2016
DOI: 10.1007/s11011-016-9928-5
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of a patient with ethylmalonic encephalopathy by intravenous N-acetylcysteine

Abstract: Ethylmalonic encephalopathy (EE) is an autosomal recessive devastating metabolic disorder affecting the brain, gastrointestinal tract, peripheral vessels and rarely the other vascular organs. We report a 10-month-old girl who presented as a meningococcemia clinic but later diagnosed ethylmalonic encephalopathy. Molecular analyses revealed a homozygous c.554 T > G; p. L185R mutation in ETHE1 gene. She was only partially benefited from riboflavine, coenzyme Q10, metronidazole, N-acetylcysteine and symptomatic tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…Interestingly, the different ETHE1 deficient fibroblast cell lines showed some heterogenous alterations that could be at least partially explained by the different mutations. However, even different cell lines with the same mutation (ETHE1-1 and ETHE1-4) showed some variability in mitochondrial function, consistent with previous conclusions that there is no clear genotype-phenotype correlation in this disease 80–82 . The reasons for these variations and their correlation with clinical symptoms remain to be clarified, and may ultimately be useful for the identification of additional specific therapies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Interestingly, the different ETHE1 deficient fibroblast cell lines showed some heterogenous alterations that could be at least partially explained by the different mutations. However, even different cell lines with the same mutation (ETHE1-1 and ETHE1-4) showed some variability in mitochondrial function, consistent with previous conclusions that there is no clear genotype-phenotype correlation in this disease 80–82 . The reasons for these variations and their correlation with clinical symptoms remain to be clarified, and may ultimately be useful for the identification of additional specific therapies.…”
Section: Discussionsupporting
confidence: 88%
“…These findings are particularly interesting since previous data showed that JP4-039 crosses brain-blood barrier in mice 78 and ETHE1 and MOCS1 deficiencies are inborn errors mainly characterized by neurological dysfunction. Furthermore, N -acetylcysteine, an antioxidant currently used to treat ETHE1 deficient patients 10,13,79,80 , did not affect superoxide levels, demonstrating the importance of mitochondrial targeting for the biological efficacy of free radical scavengers.…”
Section: Discussionmentioning
confidence: 96%
“…A resemblance of some EE biochemical features with ACADs and complex IV deficiency may have encouraged treatment with riboflavin. While some reports find no effect of riboflavin [98,[100][101][102][103][104][105][106][107], a number of reports suggest some level of positive effect [99,[108][109][110][111][112]. However, the therapeutic effect of riboflavin is difficult to interpret since most studies have used riboflavin in combination with other vitamins or cofactors.…”
Section: Ethylmalonic Encephalopathymentioning
confidence: 99%
“…Since the supplementation of NAC replenishes the intracellular pool of reduced glutathione, the sulfide is effectively buffered. NAC supplementation is currently used in patients with ethylmalonic encephalopathy [ 198 , 199 , 200 ], with encouraging results.…”
Section: “One-size-fits-all” Approachesmentioning
confidence: 99%